Determinants of anemia among children under five in Eastern Uganda: a community-based cross-sectional study - Joel J. Komakech; Edirisa J. Nsubuga; Jessica M. Graves; Oladayo E. Apalowo; Rahel Mathews; Leah B. Pylate (Frontiers in Public Health)
BackgroundAnemia is a leading contributor to child morbidity and mortality in Sub-Saharan Africa. In Uganda, more than half of the children under 5 years are affected by anemia. Understanding context-specific determinants remains critical for targeted interventions. This study examined the community prevalence and factors associated with anemia among children aged 6–59 months in the Busoga Region of Uganda.MethodsThis community-based cross-sectional study included 439 caretaker-child dyads with children aged 6–59 months. Multistage random sampling was used to select households, and one eligible child was recruited. A pre-tested electronic face-to-face interviewer-administered questionnaire was used to collect the data. Capillary blood samples from each child were obtained through a finger or heel prick, and hemoglobin concentration was measured using standardized HemoCues. The United Nations Children's Fund (UNICEF) cut-offs were used to determine anemia status among children after adjusting for altitude. Bivariate and multivariable Modified Poisson Regression tested the association between key demographic variables and child anemia using unadjusted and adjusted prevalence ratios (APRs). Variables with p ≤ 0.2 at bivariate analysis were included in the multivariate regression models, using a backward stepwise method. Covariates with p < 0.05 were considered risk factors for anemia.ResultsThe mean age of the caretakers was 31 ± 11 years, with only 19 (4.3%) males. More than half (52.0%) of the children were male. Among the sampled children, 229 (52.2%) had a history of malaria, 212 (48.3%) were not dewormed, 296 (67.4%) were anemic, 22 (5.0%) had severe anemia, and 161 (36.7%) had moderate anemia. Children had a higher risk of anemia if they had a history of malaria (APR = 1.2 [1.1–1.4], p = 0.023), and had a caretaker aged between 45 and 59 years (APR = 1.5 [1.1–2.1], p = 0.025). Conversely, children aged 36-47 and 48-59 months (APR = 0.6 [0.5–0.8], p = < 0.001, and APR = 0.6 [0.5–0.8], p = 0.006, respectively) were less likely to be anemic.ConclusionsAnemia among children is a severe public health problem in the Busoga Region. It was associated with having a history of malaria, child age, and caretaker age. Interventions such as the distribution of long-lasting insecticidal nets, malaria vaccination, chemoprophylaxis, and sensitization of caregivers on adequate child feeding practices could reduce the anemia burden in the region.